2009
DOI: 10.1021/bi900064t
|View full text |Cite
|
Sign up to set email alerts
|

CoCl2Induces Apoptosis via the 18 kDa Translocator Protein in U118MG Human Glioblastoma Cells

Abstract: The 18 kDa translocator protein (TSPO), formerly known as the peripheral-type benzodiazepine receptor, has been reported to be closely associated with the mitochondrial permeability transition pore (MPTP). TSPO is believed to exert pro-apoptotic functions via modulation of MPTP opening. Cobalt chloride (CoCl(2)), which is sometimes used as a hypoxia mimicking agent, is also known to be able to induce apoptosis. One of our questions was whether CoCl(2) may induce apoptosis via the TSPO. To address this question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
116
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(132 citation statements)
references
References 49 publications
16
116
0
Order By: Relevance
“…20, 21 We here demonstrate that when the ratio of TSPO to VDAC1 increases, mitochondrial production of ATP is limited and ROS levels are increased (Fig. 6), evidence that is consistent with previous publications.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…20, 21 We here demonstrate that when the ratio of TSPO to VDAC1 increases, mitochondrial production of ATP is limited and ROS levels are increased (Fig. 6), evidence that is consistent with previous publications.…”
Section: Discussionsupporting
confidence: 92%
“…6), evidence that is consistent with previous publications. 10,20,21 By influencing the cellular redox system, TSPO blocks the ubiquitination of mitochondrial proteins, essential for effective recruitment of the autophagosomal machinery via SQSTM1. 52 Cells largely devoid of TSPO show indeed an upregulation of mitochondrial ubiquitination with the same being observed in PRKCE ¡/¡ MEFs (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, its cardioprotective effect was documented through its ability to release hydrogen sulfide in the mitochondria [12] . CoCl 2 is effective in inducing ROS via mitochondria [32] and our results with STS on this model demonstrate that the drug has the potential to scavenge ROS effectively, when it was given along with cobalt chloride. Interestingly, the absence of difference between the subpopulation in the ROS scavenging ability emphasizes the relationship between the functional difference of IFM and SSM with respect to their location.…”
Section: Resultsmentioning
confidence: 51%
“…Notably, wild type rats are not prone to develop atherosclerosis even when subjected to HFHC diet (Dimitrova-Shumkovska et al, 2010a). We have shown that reduction of TSPO expression by genetic manipulation in vitro in cell culture reduces mitochondrial ROS generation (Veenman et al, 2008Zeno et al, 2009). We have discussed previously that the reduced TSPO levels accompanying atherogenic challenges may be a compensatory mechanism to counteract oxidative stress in the aorta and liver (Dimitrova-Shumkovska et al, 2010 a, b, c).…”
Section: Discussionmentioning
confidence: 94%